MIRERC 066/2025: Modelling Pneumonia Transmission Incorporating Asymptomatic Component and Media Awareness. - Douglas Kubania, Mwenda; Dr. Grace Gakii Muthuri; Dr. Stephen Karanja (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Pneumonia is a form of acute respiratory infection that affects the lungs. Pneumonia is a major cause of death, particularly in children under five and the elderly. It ranks as one of the top causes of death globally. The Kenya Health Information System data indicates a substantial increase in reported cases. Pneumonia cases rose from 477,186 in 2020/2021 to 793,864 in 2022/2023. Controlling pneumonia remains a significant challenge, especially due to its ability to spread through symptomatic and asymptomatic carriers. Notably, the existing mathematical models have given asymptomatic carriers less focus. This study considers media awareness as a behavioural intervention that can be used to provoke asymptomatic carriers to get screened and receive treatment. The main aim of this study is to develop a mathematical model that describes pneumonia transmission dynamics, incorporating the asymptomatic component and the impact of awareness programs. A population-based compartmental approach will be used to formulate the models, which culminate in systems of differential equations. The entire population(N) is divided into seven compartments: The Susceptible(S), Exposed(E), Infectious symptomatic (Is), Infectious asymptomatic(Ia), Treated symptomatic(Ts),Treated asymptomatic(Ta), and the Recovered(R). Reproduction numbers will be determined from the eigenvalues of the next-generation matrix. Numerical simulations of the ordinary differential equations will be done using MATLAB software to determine the impact of awareness levels on asymptomatic individuals. The results of this study will stimulate discussions and a review of the current assumptions concerning the role of asymptomatic carriers in disease spread. This will, in turn, strengthen decision-making among health care officials regarding targeting asymptomatic infectious pneumonia patients in an endeavor to fight epidemics of this disease.